1989
DOI: 10.1136/bmj.299.6690.25-a
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric rehabilitative care after fractures of the proximal femur: one year follow up of a randomised clinical trial.

Abstract: We investigated the use of amniocentesis performed at eight to 14 weeks' gestation as a possible alternative to chorionic villus sampling. Patients, methods, and results Samples of amniotic fluid were taken from 40 gestation, and the mean time to the cells being harvested was 12 6 days. In contrast only 17 (68%) of the 25 samples taken at eight to 11 weeks yielded a result. One sample taken at 13 weeks' gestation yielded a female karyotype, whereas the fetal parts revealed a male karyotype; the sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Kennie et al found that women with hip fracture who were admitted to a geriatric ward after surgery had a shorter median stay and were less likely to be discharged into institutional care than women who remained on an orthopaedic ward 30. After one year the mortality was lower and more patients were living independently 31. However, the patients in the control group were older and had more severe cognitive impairment than those in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Kennie et al found that women with hip fracture who were admitted to a geriatric ward after surgery had a shorter median stay and were less likely to be discharged into institutional care than women who remained on an orthopaedic ward 30. After one year the mortality was lower and more patients were living independently 31. However, the patients in the control group were older and had more severe cognitive impairment than those in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Standardised care pathways designed and rolled out to meet these demands have shown inconsistent results for patient benefit and functional improvements. 23,121,128,157,238,239 When they were reported to improve patients' functional outcomes 46,95,100,102,140,155,218,237 or quality of life, 100,144 or to reduce morbidity or mortality, 100,124 the trade-off was usually a longer hospital stay, leading to increased cost and resource implications. 124,155 One element that was important in attaining better outcomes was discharge planning that took into account patients' self-care information and education needs.…”
Section: Discharge Planningmentioning
confidence: 99%
“…Multidisciplinary care pathways have improved patient care and functional outcomes 46,102,155,237 and quality of life 144 and reduced morbidity or mortality, 124,159 but their successful execution requires the completion of successive steps by a chain of professionals. Non-completion or partial completion of tasks in the pathway led to delays in patient care and the risk of litigation.…”
Section: Care Manager 176mentioning
confidence: 99%
“…The methods used in these studies differed considerably in aims, interventions, and outcomes, producing inconsistent and conflicting results [43][44][45][46]. According to a recent meta-analysis, there is no conclusive evidence that co-ordinated multidisciplinary inpatient rehabilitation is more effective than conventional hospital care (no rehabilitation professionals involved) for older patients with hip fracture [47].…”
Section: Role Of Exercise For Musculoskeletal Rehabilitation After Himentioning
confidence: 95%